Challenges in Teaching English for the Deaf Students - Ristiani, Aris (ELLITE, 2018)
English is a subject included in the education curriculum in Indonesia.According to the individuals with Disabilities Education Act (IDEA), one of thecategories of students with special needs is deaf students. This paper is aimedto discover the challenges faced by deaf students’ teachers in teaching Englishand the strategies to cope with those challenges based on relevant theoriesand previous studies. The finding showed that teachers experienced severalchallenges in teaching the deaf students such as getting students’ attention,understanding words from students’ lip movements, giving definitions andexample, differentiating similar words in different contexts, and deliveringmaterials related to students prior knowledge. The strategies to cope thosechallenges are asking students to prepare dictionaries, using alphabetic signs,waving or patting students’ shoulders to get their attention. In addition it alsorequires teaching model and professional teacher to be creative and effectivein teaching English for the deaf students.